Optimasi Konsentrasi Pati Biji Alpukat (Persea Americana M.) Dan Kitosan Menggunakan RSM Terhadap Sifat Barrier Edible Film - Indira Andria Putri; Anak Agung Istri Sri Wiadnyani; I Nengah Kencana Putra (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Edible films are thin, consumable layers used as food packaging, typically made from starch. One of high-amylose starch source is avocado seed starch. However, starch-based films generally exhibit high water vapor transmission rate and water uptake, which are indicators of edible film with poor barrier properties because the film becomes more easily permeated by water vapor and absorbs excess water, making it unable to protect the product effectively. Therefore, chitosan incorporation is required to reduce both WVTR and water uptake in the edible film by forming a denser film matrix. This interaction reduces overall porosity and effectively decreases permeability to water vapor. With an experimental strategy based on Central Composite Design (CCD), this study aimed to ascertain the optimum concentrations of chitosan and avocado seed starch using Response Surface Methodology (RSM) in connection to the water barrier properties of edible films. The result showed that 3.93 percent avocado seed starch and 0.41 percent chitosan were the optimum conditions. According to a validation test of the optimum condition carried out under these circumstances. After testing, the edible film with the best barrier properties had a tensile strength of 3,90 MPa, elongation at break of 32 percent, thickness of 0.15 mm, and a light reddish-brown color characterized by L*=68.91, a*=7.94, and b*=17.65.